The Effect of Human Resource Management on Waste Management Effectiveness With Organizational Commitment as a Mediating Variable in Kepenuhan Tengah Village - Bachtiar, Ahmad Arif; Rahmat, Adi; Munthe, Richa Afriana (Jurnal Indonesia Sosial Sains, 2026)
This study aims to analyze the influence of human resource management on the effectiveness of waste management with organizational commitment as a mediating variable in Kefullan Tengah Village. This study uses a quantitative approach with a total of 160 respondents, consisting of cleaners, village officials, RT/RW chairs, and the community. The data was analyzed using SmartPLS 4.0 to see the direct and indirect influence between variables. The results of the study show that HR management has a significant effect on organizational commitment and the effectiveness of waste management. Organizational commitment has also been proven to have a significant effect on the effectiveness of waste management. However, the indirect influence of HR management through organizational commitment to waste management effectiveness is not significant, indicating that the role of organizational commitment as a mediator has not been optimal. These findings imply that strengthening HR management, such as training, coaching, and rewarding, has a greater direct impact on the effectiveness of waste management. In addition, increasing organizational commitment is still important to be carried out as a support for the success of the cleanliness program at the village level. This research is expected to be a reference for local governments in improving the effectiveness of public services, especially in the field of waste management.